1963
DOI: 10.1017/s0022029900011626
|View full text |Cite
|
Sign up to set email alerts
|

Section B. Cheese and butter starters

Abstract: Leuconostoc cremoris is used throughout the text in preference to Leuc. citrovorum or Betacoccus cremoris, see p. 422.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1967
1967
1993
1993

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 231 publications
0
11
0
Order By: Relevance
“…Our results with the purified phage lysin showed that the enzyme is specific to groups N and D streptococci, none of the other serological groups of streptococci being lysed; it lyses viable and heat killed cocci or their cell walls (in contrast to egg white lysozyme) (Reiter & Oram, 1963;Oram & Reiter, 1965. Fig.…”
Section: (I) Purification Of Phage Zysin and Its Activitymentioning
confidence: 74%
See 3 more Smart Citations
“…Our results with the purified phage lysin showed that the enzyme is specific to groups N and D streptococci, none of the other serological groups of streptococci being lysed; it lyses viable and heat killed cocci or their cell walls (in contrast to egg white lysozyme) (Reiter & Oram, 1963;Oram & Reiter, 1965. Fig.…”
Section: (I) Purification Of Phage Zysin and Its Activitymentioning
confidence: 74%
“…Brock (1962) (1967) showed that chloramphenicol mutants of Group A streptococci developed simultaneously a non-specific resistance to phage. Preliminary attempts to prove this for group N streptococci (Reiter, 1967a) were only partially successful, but warrant further investigation. Later, the phage resistance of chloramphenicol resistant starter was confirmed by Erskine (1970a).…”
Section: Phage Resistant Mutantsmentioning
confidence: 99%
See 2 more Smart Citations
“…This requires techniques for the rapid and reliable identification of starter strains. Usually conventional methods such as physiological [2,4] and immunological [5,6] tests, phage resistance [7] tests, or more modern techniques such as the analysis of protein patterns, enzyme expression [8] or plasmid profiles [9] are used for strain identification. Some of these methods are heavily influenced by growth conditions and the physiological status of the particular organisms.…”
Section: Introductionmentioning
confidence: 99%